Molecular Detection of Candidatus Rickettsia andeanae and Ehrlichia sp. in Amblyomma pseudoconcolor Aragão, 1908 (Acari: Ixodidae) from the Argentinian Patagonia - Sebastian, Patrick Stephan (2022)
Fil: Winter, Marina. Universidad Nacional de Río Negro, Sede Atlántica. Centro de Investigaciones y Transferencia de Río Negro (CONICET-UNRN), Río Negro; Argentina.